876 Veriset Haemostatic Patch, Indications, Benefits and Complications: A Systematic Review. (19th August 2022) - Zhang, J; Zhou, A; Jawaid, A; Adebayo, O; Hashmi, Y; Krkovic, M; Ahmed, Z
Abstract: Aim: Achieving haemostasis intraoperatively is important for minimising blood loss, complications, and operation time. Suturing, cauterisation, fibrin glues and patches are used for this purpose. We explore Veriset, a patch consisting of polyethylene glycol and oxidised cellulose, to determine and compare its safety and effectiveness. Method: Medline, Embase, Web of Science, Scopus, Cinahl and Cochrane databases were searched. Data points collected were Study/subject characteristics/demographics, surgery/specialty, time to haemostasis, proportion of haemostasis achieved, intraoperative adverse events, post operative complications, follow up time, and biochemical/histological analysis. Risk of Bias was assessed by Newcastle-Ottawa Scale Results: Six studies were included; four human trials (3 RCTs, 1 case series) and two animal trials. The human trials combined had 250 patients, with 147 using Veriset. In two RCTs, Veriset showed faster time to haemostasis and higher proportion of haemostasis achieved vs suturing and Tachosil haemostatic patch. In all three RCTs, no significant differences in adverse events and complications were seen between Veriset and suturing/Tachosil. Vascular, nephrectomy and hepatic surgery were investigated. In the animal studies, the pig trial showed similar effectiveness and safety as the human trials. The rat study compared novel experimental patches to Veriset, and showed similar effectiveness to Veriset, at reduced costs. Conclusions: Although current literature is scarce, Veriset is more effective than alternatives for haemostasis, with similar safety, although there are now other experimental patches that could have better health economic implications. Further clinical trials would be necessary to determine the breadth of applicable surgical fields for Veriset.